TINJAUAN PUSTAKA SISTEMATIS: PENDIDIKAN KARAKTER BERBASIS DONGENG DI SEKOLAH DASAR - Khotimah, Siti Khusnul; Rahmawati, Fitri Puji (Jurnal Holistika, 2024)
This study examines the values of character education, as well as the strategies and outcomes of story-based education implementation in elementary schools. This study uses a systematic literature review as its methodology. The literature review process involves searching for relevant articles, evaluating them using data extraction, and then comparing the results of the literature. Google Scholar was the data source used. The research results indicate that (1) the values of character education in elementary school fairy tales include honesty, discipline, social concern, and responsibility; (2) the strategies used in character education through fairy tales in elementary schools include reading and listening habits that teachers implement, which can more easily shape students' character through storytelling activities; (3) the outcomes of implementing character education through fairy tales in elementary school students show attitudes reflecting character values, such as enthusiasm for reading books. In addition, storytelling activities are very effective in implementing character education in elementary schools. The implications of this research are, first, that teachers should diligently provide character education through the habit of reading fairy tales in elementary schools. Second, parents can follow up on the programs implemented in elementary schools by making it a habit to read fairy tales to their children.